Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)

The Agenda for Prosperity: Road to Middle Income Status - Government of Sierra Leone (2013)
Keywords: ⛔ No DOI found

Republic of Sierra Leone Higher and Tertiary Education Sector Policy Note - World Bank (2013)

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...